Single Mutations in the Transmembrane Domains of Maize Plasma Membrane Aquaporins Affect the Activity of Monomers within a Heterotetramer - Berny, Marie C.; Gilis, Dimitri; Rooman, Marianne; Chaumont, François (Molecular plant, 2016)
Aquaporins are channels facilitating the diffusion of water and/or small uncharged solutes ecross biological membranes. They assemble as homotetramers but some of them also form heterotetramers, especially in plants. In Zea mays, aquaporins belonging to the plasma membrane intrinsic protein （PIP） subfamily are clustered into two groups, PIP1 and PIP2, which exhibit different water-channel activities when expressed in Xenopus oocytes. When PIP1 and PIP2 isoforms are co-expressed, they physically interact to modulate their subcellular localization and channel activity. Here, we demonstrated by affinity chromatography purification that, when co-expressed in Xenopus oocytes, the maize PIP1;2 and PIP2;5 isoforms assemble as homo- and heterodimers within heterotetramers. We built the 3D structure of such heterotetramers by comparative modeling on the basis of the spinach SoPIP2;1 X-ray structure and identified amino acid residues in the transmembrane domains which putatively interact at the interfaces between monomers. Their roles in the water-channel activity, subcellular localization, protein abundance, and physical interac- tion were investigated by mutagenesis. We highlighted single-residue substitutions that either inactivated PIP2;5 or activated PIP1;2 without affecting their interaction. Interestingly, the Phe220Ala mutation in the transmembrane domain 5 of PIP1 ;2 activated its water-channel activity and, at the same time, inactivated PIP2;5 within a heterotetramer. Altogether, these data contribute to a better understanding of the interaction mechanisms between PIP isoforms and the role of heterotetramerization on their water-channel activity.